Building Adaptive Capacity Through Civic Environmental Stewardship: Responding to COVID-19 Alongside Compounding and Concurrent Crises - Landau, Laura F.; Campbell, Lindsay K.; Svendsen, Erika S.; Johnson, Michelle L. (Frontiers in Sustainable Cities, 2021)
A growing body of community resilience literature emphasizes the importance of social resources in preparing for and responding to disturbances. In particular, scholars have noted that community based organizations and strong social networks positively contribute to adaptive capacity, or the ability to adjust and respond to change while enhancing the conditions necessary to withstand future events. While it is well established that strong civic engagement and social networks contribute to enhanced adaptive capacity in times of change, there is more to learn about how adaptive capacity at the civic group and network level is impacted temporally by multiple and compounding crises. Research has shown that the ability for communities to adapt and respond to crisis is closely tied to longer term recovery. In the midst of the COVID-19 pandemic, which has overlapped and intersected with multiple additional climate crises as well as a reigniting of the ongoing American reckoning with racial injustice, the ability for communities to adapt and respond to compounding crises seems more crucial than ever. This paper uses qualitative data from semi-structured interviews with 34 civic environmental stewardship groups in New York City to explore their role in building adaptive capacity. In order to better understand how past crises have impacted stewardship groups’ response to COVID-19, we focus on how groups have demonstrated flexibility and learning at an organizational scale. We look at two other crises, both acute (Superstorm Sandy, which hit the East Coast in 2012) and chronic (systemic racism) to identify instances of learning that lead to organizational transformation. We further aim to understand how group professionalization, measured by budget and staff size, and network connectivity impact their actions. By comparing the groups’ experiences and responses to each event, we uncover strategies learned from past events (e.g. sharing contact lists, holding internal dialogues, leveraging new funding sources) that enable stewardship groups to respond to disaster in a way that builds their organizational adaptive capacity as well as contributes to the long-term resilience of their communities.